Doege Potter syndrome - Zainulabid, Ummu Afeera; Abdul Razak, Megat Razeem; How, Soon Hin; Ibrahim, Aishah; Md Salleh, Nor Hafliza; Othman, Noriah; Mohamed, Dahlia (2018)
Pleuropulmonary solitary fibrous tumor (SFT) infrequently have been associated with paraneoplastic syndromes, most commonly reported is non islet cell tumor hypoglycaemia (Doege Potter Syndrome).